(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, both the product-normed linear space P-NLS (product-Banach space) and product-semi-normed linear space (product-semi-Banch space) are introduced. These normed linear spaces are endowed with the first and second product inequalities, which have a lot of applications in linear algebra and differential equations. In addition, we showed that P-NLS admits functional properties such as completeness, continuity and the fixed point.